The literature that drives the work of Lia Rodrigues - Adriana Pavlova (Revista Brasileira de Estudos da Presença, 2021)
The literature that drives the work of Lia Rodrigues1 - This article presents the readings that inspired the work of choreographer Lia Rodrigues (1956), starting in the 1990s and ending with her 2016 piece, For the sky not to fall. The study lists works of fiction and non-fiction, including literature, philosophy, and anthropology, which served as triggering devices for the works’ dramaturgies, while still not seeking to translate the written word in linear or narrative form into dance. The analysis presents this choreographic unfolding, which eschews a conventional reading, to achieve bodily states in the dancers. The collection of readings is presented in relation to the company’s repertoire, proposing dialogues between text fragments and dance.